Cultural Entertainment Consumption and Empathy Communication Mechanism - Zhang, Wenming (Frontiers in psychology, 2022)
The economic and cultural effects of sports films have attracted close attention from academia as well as the industry. In this paper, two sub-studies were conducted to explore the empathy mechanism performance of the interest-related community in sports films. In Study 1, the film Lead was applied as an example and used network text analysis to analyze the discourse characteristics and structure of its interest-related community to grasp the practice regularities. More specifically, the results in Study 1 show that the theme feature, brand building, technological innovation, and spirit communication are the key factors that affect an individual's empathy for sports films. In Study 2, I conducted a survey to explore the empathy mechanism of sports films in the new age to provide a theoretical reference for the high-quality development of films. The above-mentioned four main factors have positive impacts on empathy: affective empathy and cognitive empathy.